Transformation of Social Media and Information Technology in SMEs: The Critical Role of Industry-Academia Partnership in Human Resource Development - Azzaakiyyah, Hizbul Khootimah; Wanof, M. Indre; Fitri, Wahyuni Shalatan; Almaududi Ausat, Abu Muna; Shafiq, Muhammad Aqib (CV. Media Digital Publikasi Indonesia, 2024)
The advancements in information and communication technology, particularly social media, have globally reshaped the business landscape. SMEs are expected to leverage these technologies to expand their markets, enhance operational efficiency, and strengthen customer relationships. This research aims to identify the critical role of industry-academia partnerships in supporting the transformation of social media and information technology in SMEs. The study employs a qualitative approach with a literature review method. Data for this research are sourced from scholarly articles indexed by Google Scholar from 2013 to 2024. The findings indicate that the transformation brought by social media and information technology has profoundly changed how SMEs operate. Through the adoption of social media platforms like Facebook and Instagram, as well as e-commerce technologies, SMEs can extend their market reach, reinforce brand identity, and enhance direct interaction with potential customers at minimal costs. Information technology also supports efficiency in inventory management, order processing, and market analysis. Despite challenges such as technological skill gaps, partnerships among industry, academia, and government are crucial in enabling SMEs to optimally utilize these technologies